10.7k views
4 votes
Find the quotient (a) x^n-1 ÷ x-1 for n = 2, 3, 4, and 8 (b) What patterns do you notice? (c) Use your work in part (a) to write an expression equivalent to x^n-1 ÷ x-1 for any integer n > 1.

User Cske
by
5.8k points

1 Answer

7 votes

Answer:

(a)
(x^(2) -1)/(x-1) =1+x


(x^(3) -1)/(x-1) =1+x+x^(2)


(x^(4)-1 )/(x-1) =x^(3)+x^(2)  +x+1


(x^(8)-1 )/(x-1) =x^(7)+x^(6)+x^(5)+x^(4)+x^(3)+x^(2)+1

(b) when we divide (
x^(n) -1) with (x-+1) then the quotient will be a polynomial of x with (n-1) degree and all the coefficients are 1.

(c)
[1+x^(2) +x^(3)+x^(4)+x^(5)+.....+x^(n-2) +x^(n-1) ]

Explanation:

(a) We have,
(x^(2) -1)/(x-1) =((x-1)(x+1))/(x-1) =1+x (Answer)

and,
(x^(3) -1)/(x-1) =((x-1)(x^(2)+x+1) )/(x-1)=1+x+x^(2) (Answer)

and,
(x^(4)-1 )/(x-1) =((x-1)(x+1)(x^(2)+1) )/(x-1)=(x+1)(x^(2)  +1) =x^(3)+x^(2)  +x+1 (Answer)

and,
(x^(8)-1 )/(x-1) = ((x-1)(x+1)(x^(2)+1)(x^(4) +1) )/(x-1) =(x+1)(x^(2)+1)(x^(4) +1) =x^(7)+x^(6)+x^(5)+x^(4)+x^(3)+x^(2)+1 (Answer)

(b) From the above four quotients it is clear that when we divide (
x^(n) -1) with (x-+1) then the quotient will be a polynomial of x with (n-1) degree and all the coefficients are 1. (Answer)

(c) Hence, from the above pattern of the quotients we can write the expression which is equivalent to
(x^(n)-1 )/(x-1) will be


[1+x^(2) +x^(3)+x^(4)+x^(5)+.....+x^(n-2) +x^(n-1) ] (Answer)

User WooWaaBob
by
5.6k points